The Phenomenon Of Toxic Relationship Among Students - Salmatuanisa, Fani; Wahyuni, Tita; Siswoyo, Mukarto; Lestari, Aghnia Dian (Journal of Social Research, 2024)
Humans are created as social creatures that will not be separated from a life that needs each other. Because humans actually need help from others, every individual does not always get the same treatment from someone. Toxic Relationship is an event when you feel hurt, feel disadvantaged, feel uncomfortable, feel insecure, lack of affection, and the victim feels intimidated. The impact can flatten fear and traumu and make it difficult to interact socially. The method used in this study is qualitative with a phenomenological approach by explaining the phenomenon of experience that has been carried out by one of the individuals experienced with real events. The object was obtained by several subjects with data sources coming from interviews and data analysis was carried out by data reduction, presenting data and drawing conclusions. The results of this study are two forms of violence, namely verbal violence and physical violence. Most of the problems obtained are about the bad treatment of their partners. This causes the victim to feel inferior and triggers his mental health.